Long-term studies of Crozet Island killer whales are fundamental to understanding the economic and demographic consequences of their depredation behaviour on the Patagonian toothfish fishery - Guinet, Christophe; Tixier, Paul; Gasco, Nicolas; Duhamel, Guy (ICES Journal of Marine Science, 2014)
Abstract This paper provides a synthesis of results obtained as part of a long-term collaborative study involving biologists, fishers, and resource managers—centring on the occurrence of killer whales in the Crozet Archipelago before and after the implementation of a demersal longline fishery for Patagonian toothfish. Depredation behaviour was reported as soon as the fishery was initiated, with dramatic effects on both the demographic trajectories of the killer whales and on the amount of fish lost by the fishers. Killer whales interacting with the fishery exhibited very high mortality rates when illegal fishing took place, while killer whales not interacting were unaffected. However, after illegal fishing ended, killer whales interacting with the fishery exhibited both higher fecundity and survival rates compared with killer whales not interacting. Since whales typically removed fish entirely from the hooks, an adapted methodology that did not rely on determining the number of damaged fish was developed to estimate depredation rates. In the Crozet EEZ over a 10-year period, 33.9% of the total amount of Patagonian toothfish caught, representing a total of 28 million €, was estimated to be lost due to the combined effects of killer whale and sperm whale depredation. In an effort to reduce depredation losses, modifications to fishing methods, such as changing the fishing season, changing fishing areas when exposed to depredation and changing longline length and hauling speed were successfully tested. Acoustic deterrent devices were ineffective in deterring killer whales from depredating longlines. Alternative fishing gears, such as fish pots, were also tested. However, while providing encouraging results regarding the suppression of depredation and seabird bycatch, fish pots were not efficient enough to sustain an economically viable fishery. In conclusion, we discuss how the findings of this comprehensive study can be used elsewhere in fisheries confronted with depredation.